The Effectiveness of Mindfulness as an Intervention for Stress and Anxiety Management among Professional Nursing Students Preparing for the Competency Examination (UKOM) - Ady Irawan. AM; Tatiana Siska Wardani; Agung Widiastuti; Anggie Pradana Putri (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2025)
Introduction: Professional nursing students often experience heightened academic and psychological stress, especially in preparation for the National Competency Examination (UKOM). Mindfulness-based interventions have shown promise in managing stress and anxiety effectively. This study aimed to evaluate the effectiveness of a structured mindfulness intervention on mindfulness, anxiety, and stress levels among nursing students.Method: A quasi-experimental design was employed with intervention and control groups. Participants were professional nursing students selected through purposive sampling, meeting inclusion criteria such as enrollment in the professional program and willingness to participate. The intervention group underwent eight sessions of structured mindfulness training. Outcome measures included the Five Facet Mindfulness Questionnaire (FFMQ), Zung Self-Rating Anxiety Scale (Zung-SRAS), and Perceived Stress Scale (PSS), assessed before (T1) and after (T2) the intervention. Data were analyzed using paired sample t-tests, and effect sizes were calculated with Cohen’s d.Results: The mindfulness intervention significantly improved mindfulness levels (Mean Difference = –6.00; t = –17.026; p < 0.001; Cohen’s d = 4.01), and significantly reduced anxiety (Mean Difference = 2.89; t = 16.161; p < 0.001; Cohen’s d = 3.81) and stress levels (Mean Difference = 2.50; t = 7.919; p < 0.001; Cohen’s d = 1.87). All outcomes demonstrated statistically significant and clinically meaningful improvements.Conclusions: Mindfulness intervention was significantly effective in enhancing present-moment awareness and reducing anxiety and stress among nursing students preparing for the UKOM. These findings support integrating mindfulness training as a preventive psychosocial strategy within nursing education to promote students’ mental well-being.